2015
DOI: 10.1016/j.cell.2015.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Htr2a-Expressing Cells in the Central Amygdala Control the Hierarchy between Innate and Learned Fear

Abstract: Fear is induced by innate and learned mechanisms involving separate pathways. Here, we used an olfactory-mediated innate-fear versus learned-fear paradigm to investigate how these pathways are integrated. Notably, prior presentation of innate-fear stimuli inhibited learned-freezing response, but not vice versa. Whole-brain mapping and pharmacological screening indicated that serotonin-2A receptor (Htr2a)-expressing cells in the central amygdala (CeA) control both innate and learned freezing, but in opposing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 53 publications
7
154
2
1
Order By: Relevance
“…For instance, a recent study nicely showed that a specific neuronal population in the CEA mediating innate fear to predator odor inhibits learned freezing responses to a foot-shock associated cue. This finding indicates that this neuronal population in the CEA serves as a hierarchy generator between defensive responses that prioritizes innate fear over learned fear responses (Isosaka et al 2015). In the same perspective another recent study showed that neurons in the BLA selectively mediate conditioned responses to a neutral stimulus by recruiting innate fear neurons to generate defensive responses (Gore et al 2015).…”
Section: Environment-appropriate Fear Responsesmentioning
confidence: 80%
See 1 more Smart Citation
“…For instance, a recent study nicely showed that a specific neuronal population in the CEA mediating innate fear to predator odor inhibits learned freezing responses to a foot-shock associated cue. This finding indicates that this neuronal population in the CEA serves as a hierarchy generator between defensive responses that prioritizes innate fear over learned fear responses (Isosaka et al 2015). In the same perspective another recent study showed that neurons in the BLA selectively mediate conditioned responses to a neutral stimulus by recruiting innate fear neurons to generate defensive responses (Gore et al 2015).…”
Section: Environment-appropriate Fear Responsesmentioning
confidence: 80%
“…Other areas may also contribute to the processing TMT-induced fear such as the bed nucleus of the stria terminalis (BNST; Fendt et al 2003), the lateral septum (LS; Endres and Fendt 2008), and the central amydgala (CEA; Isosaka et al 2015), as their inactivation reduces TMT-inducer fear behaviors. Lastly, a recent paper showed a specific area of the olfactory cortex, the amygdalo piriform transition area, to mediate stress hormone responses to predator odors (Kondoh et al 2016).…”
Section: Olfactory Threat Cuesmentioning
confidence: 99%
“…This further underscores the dynamic interrelationships between instinct and learning; these two forms of behavior are often intertwined in complex ways. Many instincts are further shaped by learning, and many forms of learning act on innate neural circuits (Isosaka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Isosaka et al (2015) reported that the same serotonergic cells in the amygdala control both innate and learned fear behavior in mice, but artificial inactivation of these cells upregulated the innate freezing response and downregulated the learned freezing response. Our more general transcriptomic analysis complements this in-depth analysis of a single molecular pathway, and together they show that there are common molecular substrates for both instinctive and learned behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation